Alumni Series: pharmacists to patients: a little note on the appropriate storage of medication / Mohd Shahiri Abd Ghapar - Abd Ghapar, Mohd Shahiri (Faculty of Pharmacy, 2023)
Effective management of medication storage at home is crucial to maintaining a patient's treatment over time. This is based on a previous study, where many consumers of medicines were found to practice improper methods of medication storage at home. For instance, it was discovered that they did not know the appropriate places to store their medications and instead kept them under inappropriate surroundings. They were also reported to be unaware of how the medications' stability and shelf life would be impacted by the improper storage conditions.